Cardiovascular remodelling in patients with pre-dialysis chronic kidney disease and renal transplant recipients - Ramajana Temimović; Senija Rašić; Alen Džubur (Medicinski glasnik, 2019)
Aim: To evaluate the relationship between cardiovascular remodelling and glomerular filtration rate (eGFR) in pre-dialysis chronic kidney disease (CKD) patients without cardiovascular diseases (CVD) and in renal transplant recipients (RTR). Methods: The cross-sectional study included 83 patients with eGFR<60 mL/min/1.73m 2 (45 with CKD 3 stage and 38 with CKD 4 stage). Thirty six RTR had eGFR 67.8 (57.3-73.7) mL/ min/1.73m 2 and control group consisted of 44 patients with eGFR>60 mL/min/1.73m 2. All patients were evaluated by echocardiography and X-ray. Results: Left ventricular hypertrophy (LVH) was present in 74.7% CKD patients, most frequently in CKD 4 stage and in RTR. Calcifications of abdominal aorta (CAA) were present in 87% CKD 4, 60% RTR and in 44% CKD 3 patients. Calcifications of the mitral valve were found in 34.2% CKD 4, 25.0% RTR and in 6.7% CKD 3 stage patients. Aortic valve calcifications were most frequently present in CKD 4 stage (26.3%). The LV mass index negatively correlated with eGFR (p<0.001), and positively with parathyroid hormone (p<0.001), phosphorus (p=0.043), age (p<0.001) and diabetes (p=0.043). In multivariate regression analysis the risk factor for calcifications of the mitral and aortic valve, as well as for CAA was the decline in eGFR (p<0.001). Conclusion: Renal transplant recipients have a higher incidence of CV remodelling than patients with CKD 3 and less than patients with CKD 4 stage, indicating incomplete regression of CV calcifications and LVH after kidney transplantation. A decrease of renal function represents a significant risk factor for valvular and vascular calcifications occurrence in CKD patients.
Keywords: chronic kidney disease; echocardiography; remodelling; transplantation; vascular calcification